Oral Presentations Abstracts: TOLERANCE: TOO LITTLE FOR CLINICAL ETHICS IN A PLURALIST SOCIETY? - CUMMINS, Paul J.; NICOLI, Federico (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Virtually all Western societies embrace liberalism as a political and moral; it emphasizes individual rights and liberty, democracy, autonomy, limited government, consent, pluralism, and tolerance. Clinical ethics in these societies reflects those priorities. Human migration has made Western societies more diverse and expanded the plurality of values represented within them. As a consequence, clinical ethics consultants (CEC) have encountered cases which reflect a clash between the liberal values of contemporary medical ethics and non-liberal values of patients. Because CECs are steeped in liberalism, their default attitude toward the values outside of that tradition will be tolerance. This paper will argue that because tolerance implicitly contains a judgment of inferiority to other values, it is the wrong attitude for CECs to adopt towards parties whose fundamental values clash with medical ethics. In such cases, this attitude can disrespect to the holders of the values, endorse a consequentialist compromise of values, and leave medical professionals prone to moral distress. Agonism democracy is a political philosophy that accepts that values conflicts are inevitable, and there will be winners and losers from them. It aims to channel this conflict positively by promoting a process marked by openness to questioning fundamental values and genuine consideration of (even contrary) alternate values. As an alternative to tolerance, this paper will explore if cultivating an attitude of agonism can be a better disposition for CECs in such cases. It will use a case study to compare the results of the two approaches in cases of fundamental values clash.